2013
DOI: 10.21273/horttech.23.5.613
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Grafted Tomato Production in Sandy Soils in Northern Florida

Abstract: In addition to controlling soilborne diseases, grafting with selected rootstocks has the potential to enhance growth and yields in tomato (Solanum lycopersicum) production. However, information is rather limited regarding its economic viability in different production systems in the United States. The objective of this study was to compare the costs and returns of grafted vs. nongrafted fresh-market tomato production under common management practices in fumigated fields in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 17 publications
3
32
1
Order By: Relevance
“…Table 2 presents the production costs (the same for all three treatments) in both locations. Fixed costs, harvest costs, and marketing costs were estimated based on VanSickle and Weldon (2009) and Djidonou et al (2013). The production cost included fertilizer and irrigation costs, operating costs, and fixed costs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 presents the production costs (the same for all three treatments) in both locations. Fixed costs, harvest costs, and marketing costs were estimated based on VanSickle and Weldon (2009) and Djidonou et al (2013). The production cost included fertilizer and irrigation costs, operating costs, and fixed costs.…”
Section: Resultsmentioning
confidence: 99%
“…Because material prices, weather conditions, and yields are always fluctuating, these results offer growers varied scenarios of net returns based on different conditions. Djidonou et al (2013) and Barrett et al (2012) also found that the net return difference between grafting and nongrafting became more substantial as tomato price increased. Similar patterns were observed in this data set in that the relative net profits of ASD treatments compared with CSF were very sensitive to tomato price.…”
Section: Land Preparation Costsmentioning
confidence: 90%
See 1 more Smart Citation
“…Grafted plants have expressed "grafting vigor", a concept that reflects that the phenotype of the grafted plant is more than the addition of the two separate phenotypes of the root stock and scion. Yet, although grafting increased the total cost of field-grown tomato production, the increase in marketable fruit yield may generate in some cases a significant gross economic return that may offset the cost of using grafted transplants (Djidonou et al 2013a). On the other hand, grafting increases production costs (two seeds are needed; survival rate during healing may be variable), requires skilled labor or expensive grafting equipment, and occasional results in external rooting of the scion (Lee 1994).…”
Section: Strategies For Reducing the Risk Of Nutrient Leachingmentioning
confidence: 99%
“…On the other hand, the average cost of grafted tomato plants versus non-grafted plants varies considerably depending on several factors, mainly the productive scale of the nursery, the cost of labor, the production practices, and the cost of seeds employed, which can sometimes amount to more than 50% of the total costs [7]. In nurseries with a medium-high production volume, the costs of hand-grafted plants are estimated at approximately $0.67 for the USA, compared to $0.15 for non-grafted plants [8][9][10]. Similar prices are maintained for Asian countries, such as Japan and Korea [5], while for Spain and other European countries, the costs vary between €0.54 for hand-grafted plants compared to €0.18 for non-grafted plants [11].…”
Section: Introductionmentioning
confidence: 99%